Planning for Facility Development at the Situ Cileunca Tourist Area, Bandung Regency - Ameliana, Putri Azzahra; Setyowati, Tri (Journal of Tourism Sustainability, 2025)
Situ Cileunca, a natural lake-based tourist destination in Bandung Regency, suffers from substandard tourism infrastructure and spatial disorganization. Preliminary observations reveal critical issues, including limited lodging access, degraded circulation in culinary areas, and the deterioration or absence of key facilities such as toilets, piers, observation towers, and gazebos. This study aims to develop a comprehensive facility development plan for the ±19,600 m² tourism area, aligned with spatial planning regulations and sustainable asset management principles. A mixed-methods approach was adopted, combining field observation, stakeholder interviews, and document analysis. The facility development framework is structured into three core dimensions: (1) accommodation facilities (lodging, culinary zones, playground); (2) supporting facilities (entrance gate, parking, footpaths, sanitation, security posts, waste bins, souvenir kiosks, piers, gazebos, observation towers, and photo spots); and (3) tourism auxiliary facilities (information center and signage systems). The proposed development emphasizes spatial restructuring, visual quality enhancement, and functional integration to improve visitor experience and operational efficiency. The total post-tax estimated cost for the entire project is IDR 52,239,849,498. The results contribute to formulating a replicable model for facility redevelopment in nature-based tourism destinations.